Pequenas e médias empresas de base tecnológica egressas de incubadoras paranaenses : fatores de mortalidade - Castro, Silvio César de (2006)
As from the 1990s Brazil has made a big thrust towards the establishment and development of technologically-based firms (TBF) through the introduction of technological incubators. The supply of physical and administrative infrastructure provides the program with a mechanism to minimize the business's initial impairments since difficulties are critical during the initial period of small and mediumsized firms (SMF). The literature indicates that in Brazil and abroad the mortality rates of firms that underwent the incubation process are less than those which have discarded this phase. Current analysis aims at identifying technologically-based firms' mortality factors that have undergone technologically-based incubators in the state of Paraná, Brazil. Analysis is of paramount importance due to data scarcity in Brazil on incubation programs even though the modality has been introduced more than ten years ago and in spite of the government and private money invested in technologically-based firms. Research consisted of a multiple-case analysis comprising technologically-based firms, posterior to their incubator experience, during 1999-2005, in the state of Paraná, Brazil. Data were collected by semistructured interviews. Six entrepreneurs of demised firms but which have experienced incubator processes, four directors/managers of technologically-based incubators and the president of the Paraná Incubator Network (REPARTE) were interviewed by means of pre-established schemes. Mortality rate of TBFs which had undergone incubator experience in the state of Paraná reached 13.79%. As a rule, mechanisms by the Paraná incubators to aid TBFs were similar, namely, availability of conference rooms, telephones, computers, secretaries, internet access, security, elaboration of projects for financial resources available for technology and innovation procedures. Data analyses indicated mortality factors that comprise internal or administrative and external aspects, related to incubators, regardless of the entrepreneur's control. Morta lity factors within the context of incubators included aspects mainly related to aid given to firms which had undergone incubation and the incubator's administration and management. With regard to management factors, aspects related to financial difficulties, placing of products on the market and improper production structures were identified. External factors pinpointed faults in low innovation potential products, concurrence with already consolidated firms and lack of specialized manpower.